Optimalisasi Potensi Ekonomi Lokal Melalui Inovasi Produk dan Penguatan Kemitraan Usaha - Indah Fitriana Sari; Muhammad Rafi’i Sanjani (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity was carried out collaboratively by the Faculty of Economics and Business and the Faculty of Social and Political Sciences, Universitas Teknologi Sumbawa, from February 16 to February 21, 2026. The program targeted 30 Micro, Small, and Medium Enterprises (MSMEs) in Kecamatan Sumbawa, Sumbawa Regency. The program aimed to optimize local economic potential through product innovation capacity-building and strengthening of inter-business partnerships. Participants were assessed using a pretest-posttest design to measure the effectiveness of the educational interventions. Pretest results revealed a mean knowledge score of 45.8 (out of 100) across all participants, indicating a significant gap in business management literacy. Following structured education and direct mentoring over five days, the posttest yielded a mean score of 79.3, reflecting an average improvement of 33.5 points or a gain percentage of 73.1%. The results confirmed that the combined approach of product innovation training and business partnership development significantly enhanced MSMEs' competitiveness and sustainability. MSMEs successfully developed stronger product identities, expanded market reach through digital platforms and collaborative distribution networks, and demonstrated improved confidence in applying digital marketing tools. This program concludes that integrated, evidence-based community service interventions combining product innovation, partnership management, and measured capacity building are essential strategies for strengthening the local economic ecosystem in the digital era.